Laser Micro-Processing Of Amorphous And Partially Crystalline cu45Zr48Al7 Alloy - S. N., Aqida; Brabazon, Dermot; Naher, Sumsun; Kovacs, Z.; Browne, D. (Springer-Verlag 2010, 2010)

(untitled)
This paper presents a microstructural study of laser micro-processed high-purity Cu45Zr48Al7 alloys prepared by arc melting and Cu-mould casting. Microprocessing of the Cu45Zr48Al7 alloy was performed using a Roﬁn DC-015 diffusion-cooled CO2 slab laser system with 10.6-µm wavelength. The laser was defocused to a spot size of 0.2 mm on the sample surface. The laser parameters were set to give 300- and 350-Wpeak power, 30% duty cycle and a 3000-Hz laser pulse repetition frequency (PRF). About 100-micrometer-wide channels were scribed on the surfaces of disk-shaped amorphous and partially crystalline samples at traverse speeds of 500 and 5000 mm/min. These channels were analysed using scanning electron microscopy (SEM) and 2D stylus proﬁlometry. The metallographic study and proﬁle of these processed regions are discussed in terms of the applied laser processing parameters. The SEM micrographs showed that striation marks developed at the edge and inside these regions as a result of the laser processing. The results from this work showed that microscale features can be produced on the surface of amorphous Cu–Zr–Al alloys by CO2 laser processing.